Belgopeltula belgica (Vincx & Gourbault, 1992) gen. et comb. nov. and Mudwigglus micramphidium sp. nov. from the west coast of Sweden, and reappraisal of the genus Pseudaraeolaimus Chitwood, 1951 (Nematoda: Araeolaimida: Diplopeltidae) - Holovachov, Oleksandr (European Journal of Taxonomy, 2017)
Two species of the nematode family Diplopeltidae are described from Skagerrak. The new genus Belgopeltula gen. nov. is proposed for Diplopeltula belgica Vincx & Gourbault, 1992 and is characterised by: amphidial fovea circular in female and double-loop-shaped in male; excretory pore located at the level of cephalic setae bases; oral opening on the dorsal side of the body; pharynx subdivided into strongly muscularised fusiform corpus and weakly muscularised narrow and long postcorpus; female didelphic with antidromously reflexed ovaries; supplements absent. Mudwigglus micramphidium sp. nov. is characterised by: a body of 0.6 mm long; cephalic sensilla 1.5 µm long; amphidial fovea loop-shaped, 8 µm long and 3.5 µm wide; gymnostom without cuticularised ring; tail elongate conoid, with subcylindrical distal part; terminal setae absent; spicules 15 µm long; gubernaculum present; two midventral precloacal setae. It is distinguished from M. macramphidium Leduc, 2013 in having shorter amphidial fovea, shorter spicules and presence of two precloacal setae. Redescription of Diplopeltis cylindricauda Allgén, 1932 is provided based on type material. Diplopeltula minuta Vitiello, 1972 is transferred to the genus Mudwigglus Leduc, 2013. Diplopeltis cylindricauda Allgén, 1932, Diplopeltula laminata Vitiello, 1972 and Diplopeltula cassidaignensis Vitiello, 1972 are transferred to the genus Pseudaraeolaimus Chitwood, 1951.